1995
DOI: 10.1109/77.403194
|View full text |Cite
|
Sign up to set email alerts
|

Transistor performance of high-T/sub c/ three terminal devices based on carrier concentration modulation

Abstract: Abstra&Electricfield effect devices and quasiparticle injection effect devices are good candidates for the realization of three terminal devices from high-T, materials, since they take explicit advantage of the low carrier concentration in these compounds. We describe the fabrication and operation of both types of devices, and discuss their performance as transistor-like elements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…In an alternative mode of operation, the injection of quasiparticles by the application of a gate voltage is utilized to vary the transport characteristics of the Josephson junction. This approach was taken for YBa 2 Cu 3 O 7Ϫ␦ bicrystal grain boundaries by Iguchi et al (1994) and Joosse et al (1995), and for Bi 2 Sr 2 Ca nϪ1 Cu n O 2(nϩ2) by Frey et al (1997).…”
Section: Three-terminal Devicesmentioning
confidence: 99%
“…In an alternative mode of operation, the injection of quasiparticles by the application of a gate voltage is utilized to vary the transport characteristics of the Josephson junction. This approach was taken for YBa 2 Cu 3 O 7Ϫ␦ bicrystal grain boundaries by Iguchi et al (1994) and Joosse et al (1995), and for Bi 2 Sr 2 Ca nϪ1 Cu n O 2(nϩ2) by Frey et al (1997).…”
Section: Three-terminal Devicesmentioning
confidence: 99%
“…Reference will be made to low-T c three-terminal devices primarily at the beginning, as overviews of such devices are given in [4][5][6]. Complementary overviews of high-T c three-terminal devices can be found in [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, the mechanism of current transportation across STOthin films has been investigated for c-axis oriented Au/STO/YBCO and YBCO/STO/YBCO junctions [3] with a STO barrier layer ranging from 200 to 500 nm. Analysis of the data showed that the behavior of the junctions could be well described within the framework of Mott's variable range hopping (VRH) via LS theory.…”
Section: Introductionmentioning
confidence: 99%